(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article discusses the role of the introduction of innovative technologies in the development of music education in the new stage of development of Uzbekistan and the achievement of efficiency in the field. Comparative analyzes of the programs used in teaching the field of music education are also presented